Extensive Air Showers and the LPM Effect - Alio, Lion; Diep, Pham Ngoc; Dong, Pham Ngoc; Hoai, Do Thi; Nhung, Pham Thi Tuyet; Darriulat, Pierre; Thao, Nguyen Thi (Communications in Physics, 2012)
A very simple model of thelongitudinal development of electromagnetic showers is presented,allowing for easy calculations at the highest energies where usualsimulation codes become impracticable because of the enormousmultiplicity of secondary shower particles. Shower profiles aredescribed in terms of a few parameters having Gaussianfluctuations. The model is applied to the impact of theLandau-Pomeranchuk-Migdal effect on the shower development, whichis found negligible in practical cases.